Pengaruh Model Punch (Tools)Terhadap Cacat Wrinkling Pada Proses Cup Drawing - Sharif, Wahyu Ahmad, Agus Dwi Anggono, ST., M.Eng., Ph.D, Dr. Supriyono (2015)
Research on the drawing cup aims to determine the effect of defective models punch against wrinkling and differences in cup drawing results using standard punch and punch modification, with two different materials. The initial process of designing dies, blank holder, standard punch punch followed by making modifications. Here punch modification 3 is almost like punch standard, where the difference in punch modification 3 no inner diameter as punch standard, while the punch modification 1 is almost like punch modification 2, wherein the difference in punch modification 2 no inner diameter as punch modifications 1 and differently shaped with standard or modified punch punch 3. Modification is expected to reduce wrinkling defects in the two different materials. Furthermore, the process of making the specimens in the form of aluminum and zinc plate with a diameter of 64.5 mm with a thickness of 0.2 mm. The cup material tensile testing process using ASTM E8 - 04, of the test results obtained by the value of the tensile strength of aluminum and zinc amounted to 228.185 N 1095.748 N. This test aims to determine the strength of the material draw abillity as a reference during the process of formation. Of the process of the formation of aluminum plate and zinc using a punch standard and modified can be concluded that the punch modification 1 produces cup drawing maximum with wrinkling is reduced compared to the punch standard and punch modification 2 and 3, while the worst outcomes are cup drawing produced by a modified punch 2 in which the materials undergo wrinkling and fracture (torn). The data obtained, the average power of the resulting aluminum plate produce a force of 20 KN with a punch speed of 0.0040 m / s by using lubrication cup drawing maximum yield, so that the most optimal results is to use a modified punch 1 with lubrication. It concluded that experiments using better lubrication than without lubrication.